Audit of Lestari Clinic Management Information System to Improve Patient Service Quality - Sari Putri; Irfan Gunawan; Sesi April Yeni (PT. ZIVANA CENDEKIAWAN BANGSA, 2026)
Healthcare is a fundamental societal need that demands professionalism, speed, and high accuracy in its delivery. As a primary healthcare provider, Klinik Lestari is deeply committed to delivering optimal, safe, and patient-centric care. Amidst the dynamic nature of the modern healthcare industry and rising public expectations, service quality is no longer measured solely by the competence of medical personnel but also by operational efficiency and the speed of administrative processes. Consequently, adopting information technology has become a strategic necessity to minimize human error, reduce waiting times, and integrate all business functions within the facility. Demonstrating this commitment, Klinik Lestari has implemented a Management Information System (MIS) into its daily operations. This system is designed to automate and integrate critical business processes ranging from patient registration workflows, electronic medical record (EMR) management, and queuing systems to pharmaceutical inventory and cashier transactions. In today's era of healthcare digitalization, the MIS has become the organization's backbone, influencing clinical and administrative.